A social justice alternative for framing post-compulsory education: a human development perspective of VET in times of economic dominance. (2nd April 2016) - Lopez-Fogues, Aurora
Abstract: The article provides an alternative theoretical framework for evaluating contemporary issues facing education, specifically vocational education and training (VET) in Europe. In order to accomplish this, it draws on the theoretical insights of the capability approach in the work of Amartya Sen; the concept of vulnerability as intrinsic to every human being, established by Fineman and Grear; and the concept of oppression advanced by Iris Marion Young. By developing the core concepts of each of these theories, the paper presents a human-based evaluative tool for education and argues that a fundamental misconception has arisen as to the purpose of post-compulsory education, a misconception generated by the wholesale application of the language of skills and productivity to the field of education, thus relinquishing its role to purely economic interests. The social justice framework presented herein aims to present a possible alternative approach to discuss and evaluate VET, in which humanistic concepts such as the recognition of human vulnerability and agency are central to the debate.